Factorial formulae and computer-aided research - Sušinskas, Jurgis; Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2008)
We try to demonstrate how it is possible to acquaint students with the usual computer-aided research of a mathematician.